2016 9th IAPR Workshop on Pattern Recogniton in Remote Sensing (PRRS) 2016
DOI: 10.1109/prrs.2016.7867012
|View full text |Cite
|
Sign up to set email alerts
|

Improving semantic orthophotos by a fast method based on harmonic inpainting

Abstract: Context-based modeling of 3D urban terrain has become increasingly popular in the last two decades. Typically, orthophotos are used for texturing ground. In order to increase locational awareness, it is useful to eliminate from the orthophotos those object instances which frequently appear and disappear in the terrain. Vehicles are good examples of such instances. Assuming that vehicles were detected at a previous stage of the algorithm, we developed a simple, easily parallelizable procedure on orthophoto inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In order to perform the image-based comparison to the simulation, the missing area, i.e. the sea water temperatures, had been filled in by a modification of harmonic inpainting (Kottler et al, 2016). For area 1, an interactive procedure for building outline correction using an OSM shapefile as supplementary input has additionally been performed.…”
Section: Synthetic Thermal Mapmentioning
confidence: 99%
“…In order to perform the image-based comparison to the simulation, the missing area, i.e. the sea water temperatures, had been filled in by a modification of harmonic inpainting (Kottler et al, 2016). For area 1, an interactive procedure for building outline correction using an OSM shapefile as supplementary input has additionally been performed.…”
Section: Synthetic Thermal Mapmentioning
confidence: 99%
“…The authors, however, decided to make use of context and to process not only the raw images from (Zhang et al, 2019), but also the classification results of fac ¸ade elements. In case of structure-based inpainting, (Kottler et al, 2016) demonstrated that even a simple method allows to preserve sharp edges between classes, once context information is taken into account. This paper will describe a suitable modification of the approach of (Criminisi et al, 2004).…”
Section: Image Inpainting Techniquesmentioning
confidence: 99%